THE PHENOMENON OF ONLINE PROSTITUTION THROUGH THE MI-CHAT APPLICATION IN INDRAMAYU DISTRICT - Luthfi Faisal Natsir (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
One of the social media applications that is misused as a tool for online prostitution transactions is Mi-chat or what the general public terms the